Investigating the “Public Servant Craze” Among the Post-80s Youths in Big Chinese Cities - Lu, Wei (2013)
This article studies the motivations behind the “public servant craze” among the post-80s youth in big Chinese cities like Shanghai and Beijing, as well as the antecedents of these motives. Apart from the public servant motivations (PSM) proposed by Perry and Wise in 1990, the post-80s civil servants in China also demonstrate other motives in their career choices such as job security, work-life balance, harsh employment situation, sense of achievement, to name just a few. Through semi-structured interview, I find out that there are job-specific, culture-specific and cohort-specific antecedents for these various motives. The findings stand as a supplement to the widely-accepted PSM theory and challenge the dominant belief in China that job-security is the only motive driving the public servant craze.